2008
DOI: 10.1002/pen.21035
|View full text |Cite
|
Sign up to set email alerts
|

Polyester containing isocyanate groups—Modified epoxy resin: Rheological, dynamic‐mechanical, and impact properties

Abstract: Low molar mass hydroxyl‐terminated polyester was functionalized with isocyanate groups (NCO) and used to improve the impact resistance of epoxy resin (ER) cured with triethylene tetramine (TETA). The effect of polyester‐based modifiers (with or without NCO groups) on the curing rate of epoxy/TETA system was investigated by rheological techniques. It was found that the functionalized polyester decreased the gel time, indicating an accelerating effect of the curing process. In addition, significant improvement i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The scanning electron microscope results showed rough morphology and plastic deformation in the DGEBA/polyester blends. In another work, Soares et al modified epoxy resin cured with triethylene tetramine using hydroxyl-terminated polyester containing isocyanate groups 22 . Their results showed that the added reactive polyester decreased the gel time and improved the impact strength of the epoxy network, with little detrimental effect on the glass transition temperature and stiffness.…”
Section: Preparation and Properties Evaluation Of An Epoxy Resin Tougmentioning
confidence: 99%
See 1 more Smart Citation
“…The scanning electron microscope results showed rough morphology and plastic deformation in the DGEBA/polyester blends. In another work, Soares et al modified epoxy resin cured with triethylene tetramine using hydroxyl-terminated polyester containing isocyanate groups 22 . Their results showed that the added reactive polyester decreased the gel time and improved the impact strength of the epoxy network, with little detrimental effect on the glass transition temperature and stiffness.…”
Section: Preparation and Properties Evaluation Of An Epoxy Resin Tougmentioning
confidence: 99%
“…Various studies have been carried out on the effects of solid particles such as kaolin and liquid polyesters on the mechanical properties of epoxy resins 4,[19][20][21][22] . Kaolin was used by Fellahi et al 4 as a modifier for the diglycidyl ether of bisphenol A with polyamino-imidazoline as a curing agent.…”
Section: Introductionmentioning
confidence: 99%